Redescription of Heterocerus fausti Reitter, 1879, bona species (Coleoptera, Heteroceridae) - Sazhnev, Alexey S. (Zootaxa, 2018)
The validity of Heterocerus fausti Reitter, 1879, previously considered a junior synonym of H. flexuosus Stephens, 1828 has been restored. Its redescription based upon typical material from Caucasus and additional material from Central Asia is given.